صلبی بیٹے کی بیوی کی حرمت :شرائع سابقہ اور اسلامی تعلیمات کا تقابلی مطالعہ: Sanctity of the Son's Wife: A Comparative Study of the Previous Laws and Islamic Teachings - Muhammad Abid; Saba Ghaffar; Laeeq Ahmad (International Research Journal of Arabic and Islamic Studies, 2023)
In order to establish peace and stability in the society, Allah Ta'ala has set a limit of relations between them, whether they are relatives or in-laws. In order to maintain more beauty in the family system, the prohibition and respect of relationships has been established. Rules and regulations have been set to avoid hatred and cruelty in the same family. For example, if a son marries a woman, that woman becomes forbidden to the father forever, even if the woman is divorced. In this article, the sanctity of the daughter-in-law has been researched because one of the causes of family instability in the society is disrespect and disrespect between the father-in-law and the daughter-in-law. There are clear orders regarding sanctity of daughter-in-law in previous Sharia and Islamic teachings. The disrespect and disrespect of the daughter-in-law leads to unkindness, and in the family system, evil diseases like hatred and enmity are born. Even in previous Shari'ah, death penalty has been ordered if illicit relations between father-in-law and daughter-in-law are proved.